The Ups and Downs of Plant NLR Expression During Pathogen Infection - Fick, Alicia; Swart, Velushka; van den Berg, Noëlani (Frontiers in Plant Science, 2022)
Plant Nucleotide binding-Leucine rich repeat (NLR) proteins play a significant role in pathogen detection and the activation of effector-triggered immunity. NLR regulation has mainly been studied at a protein level, with large knowledge gaps remaining regarding the transcriptional control of NLR genes. The mis-regulation of NLR gene expression may lead to the inability of plants to recognize pathogen infection, lower levels of immune response activation, and ultimately plant susceptibility. This highlights the importance of understanding all aspects of NLR regulation. Three main mechanisms have been shown to control NLR expression: epigenetic modifications, cis elements which bind transcription factors, and post-transcriptional modifications. In this review, we aim to provide an overview of these mechanisms known to control NLR expression, and those which contribute toward successful immune responses. Furthermore, we discuss how pathogens can interfere with NLR expression to increase pathogen virulence. Understanding how these molecular mechanisms control NLR expression would contribute significantly toward building a complete picture of how plant immune responses are activated during pathogen infection—knowledge which can be applied during crop breeding programs aimed to increase resistance toward numerous plant pathogens.